Development of website on General Physics subject to increase analytical skills of students - Serevina, Vina; Raihanati; Andriana, Wawan (Journal of physics. Conference series, 2020)
This research aims to develop a website on General Physics subject to increase analytical skills of students. Developed website can be used by using computer or smartphone. The ADDIE research method which are Analyzing, Designing, Developing, Implement, and Evaluating. Research was conducted in Laboratory of Media Digital atState University of Jakarta for six months, starts from November 2018 until May 2019 with students of Physics Education Program, State University of Jakarta as object of research. Indicators of analytical skill measured in this research are giving a reasoning, making a conclusion, evaluating a conclusion, predicting a conclusion, considering the validity of an argument, and explaining something using data. Students' analitycal skill improvement test was conducted by pre-test and post-test in two classes (class A and class B) with n-gain result of class A was 0,66 (medium) and class B was 0,28 (low). Results of validation test showed score 92,30% for material validation, 91,85% for media validation, and 90,37% for learning validation. According to this research result, can be concluded that developed website on general physics subject can increase students' analytical skill. All of the instruments in this research can be seen at website http://vinnarrai.com